La gestión de ventas basada en big data para la empresa de calzado “Huellas Exclusive” entre 2018-2019. - Calvopiña Bombón, Rosa Fanny (2019)
The present investigation project focuses on evaluating a sales management scheme based on Big Data that can be used by the “Huellas Exclusivas” footwear company, located in Latacunga, during the period 2018-2019. Nowadays, taking into account that companies must be more competitive and one way to achieve that goal is using the database owned by the company to analyze the customers’ behavior and to elaborate customer loyalty strategies. A bibliographic review was conducted to conceptualize sales management models, Marketing, and Big Data application as an instrument in the generation of strategies that help to improve sales management in the companies, its cost-effectiveness at an international, national and state level showing in a detailed way the applicability of this instrument above mentioned. In this process, different methodologies such as quantitative, descriptive and explanatory were used. Quantitative variables were used in the elaboration of statistic tables and graphs. Inferential and descriptive statistics were also used to check whether the implementation of strategies has improved the current sales campaign as compared to last year.The field research conducted in the company allowed gathering the information used to build a database composed of 2351 customers. The database was managed with Tableau software, from that data different graphs were obtained. Those graphs helped in the analysis of the customers' behavior in the company and also in the identification of the most relevant factors that affect the company sales level, such as, home address, the slow-seasons, model variety, brands, footwear colors, and payment methods. Also, those customers who represent 25% of the best sales were identified, different strategies regarding Father’s Day were created for them, obtaining as a result that those strategies were not appropriated. Therefore, the implementation of other strategies is necessary. That is why other activities that could be followed by the company are proposed.